Method for improving methylene blue adsorption efficiency

By using bagasse, urea and ZnCl2 to prepare nitrogen-doped porous carbon materials, the problem of low adsorption efficiency of methylene blue wastewater in the prior art is solved, and efficient and low-cost pollutant removal effect is achieved.

CN119240845APending Publication Date: 2025-01-03GUANGXI NORMAL UNIV OF SCI & TECH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411505944.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The prior art has low adsorption efficiency and high cost when treating high-concentration methylene blue wastewater, making it difficult to effectively remove methylene blue pollutants in industrial wastewater.

Method used

Using bagasse as the carbon source, urea as the nitrogen source, and ZnCl2 as the activator, nitrogen-doped porous carbon materials are prepared by pyrolysis method, which is used to adsorb methylene blue, optimize the mass ratio, carbonization temperature and time of urea to sugarcane bagasse, and form a Adsorbents with high specific surface area and pore structure.

Benefits of technology

The adsorption efficiency of methylene blue is significantly improved, especially in high-concentration solutions, the adsorption rate reaches more than 92.5%, which is low in cost, and the preparation method of adsorbent is economical.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005103956530000041
    Figure BDA0005103956530000041
  • Figure BDA0005103956530000071
    Figure BDA0005103956530000071
  • Figure BDA0005103956530000091
    Figure BDA0005103956530000091
Patent Text Reader

Abstract

The invention discloses a method for improving methylene blue adsorption efficiency, which comprises the following steps: adding an adsorbent prepared by taking bagasse as a carbon source, urea as a nitrogen source and ZnCl2 as an activating agent into a methylene blue solution with a certain mass concentration, and adsorbing for a period of time to obtain a clear solution; the mass ratio of the urea to the bagasse is (1-3): 4, and the mass ratio of the ZnCl2 to the bagasse is 2: 1. In the research of adsorbents taking bagasse and urea as raw materials, the specific surface area of the porous carbon activated by ZnCl2 is obviously increased, the pore structure is developed, and when the porous carbon is applied to a methylene blue solution with the adsorption concentration higher than 50 mg / L, the adsorption rate can reach 70% or above, which is obviously superior to that in the prior art; particularly, the porous carbon material prepared under the conditions that the mass ratio of urea to bagasse is 62.5%, the carbonization temperature is 500 DEG C and the carbonization time is 2 hours has the best adsorption rate on 100-600 mg / L of methylene blue, and the adsorption rate can reach 92.5% or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of methylene blue processing, and particularly relates to a method for improving the adsorption efficiency of methylene blue. Background Art

[0002] Methylene blue is an important organic chemical synthetic cationic dye, which is widely used in the printing and dyeing industry. It can be used for dyeing linen, silk fabrics, and paper, and can also be used for dyeing biological and bacterial tissues. The wide application of methylene blue in industry has led to the pollution of other pure water bodies by industrial wastewater containing methylene blue. The wastewater discharged by the printing and dyeing, textile and other industries has the characteristics of large water volume, complex composition, high pollution concentration and deep chroma. It has certain antioxidant and anti-biodegradability, and has become an important source of pollution in major waters in my country. Organic dye wastewater not only has high chroma, but also has high chemical oxygen demand (COD) concentration in the water, is difficult to biodegrade, and is difficult to decolorize. In addition, most dyes are toxic and have carcinogenic, teratogenic and mutagenic effects. Pollution treatment of dye wastewater is of great significance.

[0003] Since traditional treatment technologies such as chemical oxidation, biodegradation and physical flocculation have high removal rates for organic pollutants but have disadvantages such as high operating costs, the research and development of a new wastewater treatment method has become a topic of extensive research by scholars at home and abroad. Porous carbon materials are often used as adsorption materials to adsorb dyes and pigments due to their high specific surface area, complex pore structure and unique surface chemical properties. At present, coal is still widely used for production in my country. The reality is that the price of coal as a raw material does not fluctuate much and is relatively high. With the innovative development of biochar materials, the types of raw materials have gradually increased. The production of activated carbon using biomass raw materials such as sawdust, fruit shells, and straw has gradually become a research direction.

[0004] Bagasse, a renewable resource, is known for its high yield, low cost and concentrated source, and contains rich biomass energy. In today's increasingly tight energy situation, the use of bagasse as fuel has broad prospects. Sugarcane is an important raw material for making white sugar. Due to the high sugar content of sugarcane, bagasse is widely used in papermaking, textile and food processing. In the sugar-making process, sugarcane passes through the pressing workshop to squeeze the mixed juice and flows into the clarification workshop. The crushed residue after squeezing is called bagasse. Generally, sugar mills will transport it to nearby paper mills for recycling. The residual yield of bagasse is very large, accounting for 24%-27% of the total amount of sugarcane (50% of which contains water). Basically, for every ton of white sugar produced, 2-3 tons of broken residue will be produced. Therefore, the development of bagasse resources has great economic significance and environmental value.

[0005] At present, we have found an application of an adsorbent using bagasse as raw material in removing methylene blue from water. It is a preparation method of nitrogen-doped porous bagasse biochar with application number: 202311225864.9. The method first washes the bagasse raw material, crushes it and sieves it, then mixes the bagasse, urea and sodium bicarbonate, adds water, crushes it, seals it and pressurizes it, and then grinds and dries it and moves it into a covered crucible for high-temperature carbonization. After carbonization, it is cooled to room temperature, and finally washed and centrifuged to obtain bagasse biochar with nitrogen doping and rich pore structure. The invention makes full use of the thermal stripping and activation effect of the gas generated by the decomposition of urea and sodium bicarbonate, so that the bagasse fibers are eroded and stripped, and finally a bagasse biochar with nitrogen doping and rich pore structure is formed. However, the invention only treats a low concentration of 50 mg / L methylene blue organic solution, and the removal rate is only 61%. It can be seen from this that adsorbents using bagasse as raw materials still have great research prospects in the research of removing high-concentration methylene blue organic solutions. Summary of the invention

[0006] The purpose of the present invention is to solve the above technical problems and provide a method for improving the adsorption efficiency of methylene blue with low cost and high adsorption efficiency.

[0007] To achieve the above-mentioned purpose, the technical solution of the present invention is:

[0008] A method for improving the adsorption efficiency of methylene blue is to add an adsorbent made of bagasse as a carbon source, urea as a nitrogen source and ZnCl2 as an activator into a methylene blue solution of a certain mass concentration, and adsorb for a period of time at room temperature to obtain a clear solution; the mass ratio of urea to bagasse is (1-3):4, and the mass ratio of ZnCl2 to bagasse is 2:1.

[0009] As a further technical solution, the mass ratio of the above-mentioned urea to bagasse is 2.5:4.

[0010] As a further technical solution, the above-mentioned bagasse is dry bagasse.

[0011] As a further technical solution, the above-mentioned adsorbent is added in an amount of 10 to 30 mg per 100 ml of methylene blue solution.

[0012] As a further technical solution, the initial mass concentration of the methylene blue solution is 100-600 mg / L, and the pH value of the solution is 1-11.

[0013] As a further technical solution, the above adsorption time is 30 to 80 minutes.

[0014] As a further technical solution, the preparation method of the above adsorbent is:

[0015] (1) Mixing: Grind and mix bagasse and urea according to the mass ratio;

[0016] (2) Impregnation: adding water and ZnCl2 to the mixture of step (1) according to the mass ratio for impregnation;

[0017] (3) Stirring: Stir the impregnated material at room temperature and then dry it to constant weight;

[0018] (4) Carbonization: The dried material is subjected to high temperature carbonization treatment at 400-800°C for 1-3h, and then washed and dried to obtain an adsorbent.

[0019] As a further technical solution, the solid-liquid ratio of the above-mentioned mixture to water is (5-7) g:50 ml.

[0020] As a further technical solution, the time of the above-mentioned stirring at room temperature is 25 to 30 minutes.

[0021] As a further technical solution, the above-mentioned immersion time is 25 to 30 minutes.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] 1. The present invention adopts a pyrolysis method to synthesize a microporous carbon material, which has a unique morphology and good chemical stability. The material has a developed surface area pore structure and contains a large number of carboxyl, hydroxyl and other groups. After carbonization treatment, its carbon content will increase, and the pore structure will also be significantly enhanced. By adding an appropriate amount of urea, it can be converted into nitrogen element and further modified to obtain a new nitrogen-doped material with good performance. The addition of urea leads to the formation of nitrogen-containing functional groups, and carbon substances are converted into nitrogen-containing substances. Under high temperature conditions, nitrogen-containing compounds are decomposed into free radicals, which form nitrogen-containing functional groups on the carbon surface. A nitrogen-doped carbon composite material can be obtained by an amination reaction, and nitrogen is reduced by nitrogen to obtain a nitrogen-containing carbon material. The synthesized nitrogen-doped carbon presents a more significant specific surface area and mesoporous structure, which provides a wider range of possibilities for its application. The catalytic reduction reaction of organic pollutants is achieved by utilizing the hydrogen-oxygen hybrid layer generated by hydrogen bonding between nitrogen atoms and oxygen atoms in carbon molecules. The activation of ZnCl2 has the dual functions of solvent and activation pore expansion. During the high-temperature carbonization process, the doping of ZnCl2 will cause the pore structure of the carbon material to change, thereby preparing a carbon material with a good porous carbon specific surface area and a high nitrogen content. At the same time, the adsorption effect on methylene blue dye is also very significant.

[0024] 2. In the study of adsorbents using bagasse and urea as raw materials, the porous carbon activated by ZnCl2 in the present invention has a significantly increased specific surface area and a well-developed pore structure. When adsorbed on a methylene blue solution with an adsorption concentration higher than 50 mg / L, it can achieve an adsorption rate of more than 70%, which is significantly better than the prior art; in particular, the porous carbon material prepared with a urea / bagasse mass ratio of 62.5%, a carbonization temperature of 500°C, and a carbonization time of 2 h has the best adsorption rate for 100-600 mg / L of methylene blue, which can reach more than 92.5%; the adsorbent prepared under these conditions has the greatest effect on the adsorption of methylene blue when the addition amount is limited to 30 mg, the adsorption time is 1 h, the initial concentration is 400 mg / L, and the pH is 7, and the adsorption rate reaches 98.18%. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The nitrogen adsorption isotherms of different raw material samples of the present invention are shown in FIG. 1 ; GZC-U is bagasse-urea-ZnCl2, and GC-U is bagasse-urea;

[0026] Figure 2 The pore size distribution diagram of different raw material samples of the present invention; GZC-U is bagasse-urea-ZnCl2, and GC-U is bagasse-urea;

[0027] Figure 3 is an electron microscope image of bagasse (GC) of the present invention;

[0028] Figure 4 This is an electron microscope image of a sample using bagasse-urea (GC-U) as raw material in the present invention;

[0029] Figure 5 This is an electron microscope image of a sample using bagasse-urea-ZnCl2 (GZC-U) as raw material in the present invention;

[0030] Figure 6 XRD diffraction spectra of samples of bagasse (GC), bagasse-urea (GC-U), and bagasse-urea-ZnCl2 (GZC-U) of the present invention;

[0031] Figure 7 The thermogravimetric TG curves of samples of bagasse (GC), bagasse-urea (GC-U), and bagasse-urea-ZnCl2 (GZC-U) of the present invention;

[0032] Figure 8 It is the infrared spectra of samples of bagasse (GC), bagasse-urea (GC-U), and bagasse-urea-ZnCl2 (GZC-U) of the present invention;

[0033] Fig. 9 is the methylene blue standard curve;

[0034] Fig.10 This is a graph showing the effect of different urea / bagasse ratios on adsorption in the present invention;

[0035] Fig.11 This is a diagram showing the effect of different carbonization temperatures on adsorption in the present invention;

[0036] Fig.12 This is a diagram showing the effect of different carbonization times on adsorption in the present invention;

[0037] Fig.13 This is a diagram showing the effect of the amount of adsorbent added on adsorption in the present invention;

[0038] Fig.14 Graph showing the effect of the initial concentration of the methylene blue solution on adsorption;

[0039] Fig.15 This is a diagram showing the effect of adsorption time on adsorption according to the present invention;

[0040] Fig.16 Graph showing the effect of pH of the methylene blue solution on adsorption;

[0041] Fig.17 It is the pseudo-first-order kinetic curve fitting diagram of the present invention;

[0042] Fig.18 It is the fitting diagram of the pseudo-second-order kinetic model of the present invention;

[0043] Fig.19 This is a fitting curve diagram of the Langmuir isotherm adsorption model of the present invention;

[0044] Fig. 20 It is a fitting curve diagram of the Friedrich isotherm adsorption model of the present invention. DETAILED DESCRIPTION

[0045] The present invention is further described in detail below in conjunction with examples, but the implementation mode of the present invention is not limited to the scope represented by the examples.

[0046] The experimental reagents used in this embodiment are shown in Table 1:

[0047] Table 1

[0048]

[0049] 1. Pretreatment of bagasse: Place the bagasse in a drying oven and dry it to constant weight, crush, grind, and pass through a 60-mesh sieve. The sieved bagasse powder is bagged and stored for use in the preparation of the adsorbent.

[0050] 2. Preparation of adsorbent:

[0051] 1. Adsorbents with different urea / bagasse ratios

[0052] Grind and mix bagasse urea according to the mass ratio (urea / bagasse = 25%, 37.5%, 50%, 62.5%, 75%), where bagasse is 4g, urea is 1g, 1.5g, 2g, 2.5g, 3g. Add 50ml of deionized water and ZnCl2 (the mass ratio of ZnCl2 to bagasse is 2:1) to the mixture and soak it together. After soaking for 30min, place it in a heat-collecting heating stirrer and stir it at room temperature for 30min, and dry it in an electric blast drying oven to constant weight. The dried sample is placed in a tubular furnace with nitrogen, the carbonization temperature is 600℃, the carbonization time is 2h, and after the end, it is taken out and washed with deionized water and dried to obtain adsorbent samples No. 1 to 5, corresponding to urea / bagasse mass ratios of 25%, 37.5%, 50%, 62.5%, and 75%, respectively.

[0053] 2. Adsorbents with different carbonization temperatures

[0054] The mixture of urea / bagasse ratio of 62.5% (4g bagasse, 2.5g urea) was impregnated with 50ml deionized water and ZnCl2 (the mass ratio of ZnCl2 to bagasse was 2:1). After impregnation for 30min, it was placed in a heat-collecting heating stirrer and stirred at room temperature for 30min, and dried in an electric blast drying oven to constant weight. The dried sample was placed in a tubular furnace with nitrogen, and the carbonization temperature was 400, 500, 600, 700, and 800℃. The carbonization time was 2h. After the carbonization was completed, it was taken out and washed with deionized water and dried to obtain adsorbent samples No. 6 to 10, corresponding to carbonization temperatures of 400, 500, 600, 700, and 800℃, respectively.

[0055] 3. Adsorbents with different carbonization times

[0056] The urea / bagasse ratio is 62.5% (4g bagasse, 2.5g urea), 50ml deionized water and ZnCl2 (the mass ratio of ZnCl2 to bagasse is 2:1) are added and impregnated together. After impregnation for 30 minutes, it is placed in a heat-collecting heating stirrer and stirred at room temperature for 30 minutes, and dried to constant weight in an electric blast drying oven. The dried sample is placed in a tubular furnace with nitrogen, the carbonization temperature is 500℃, and the carbonization time is 1h, 1.5h, 2h, 2.5h, and 3h. After the end, take it out, wash it with deionized water, and dry it to obtain adsorbent samples No. 11 to 15, corresponding to carbonization times of 1h, 1.5h, 2h, 2.5h, and 3h, respectively.

[0057] 3. Sample Characterization and Analysis

[0058] Take a sample of pretreated bagasse and mark it as GC; take a sample with bagasse-urea as raw material (i.e. without adding ZnCl2), which is prepared according to the parameter conditions of sample No. 13, and mark it as GC-U; then take the sample No. 13 prepared as above and mark it as GZC-U.

[0059] (1) Fully automatic surface area and pore size analyzer

[0060] Samples GC-U and GZC-U were taken for adsorption and desorption tests using nitrogen adsorption method, heating and vacuum degassing. The degassing temperature was set to 300 °C and the degassing time was 10 h.

[0061] The pore structure characteristics are an important indicator of the adsorption performance of carbon materials. Figure 1 It can be seen that compared with GC-U, GZC-U has a higher adsorption capacity when the relative pressure is low p / p0<0.01, indicating that the sample has a typical microporous structure. According to the NLDFT algorithm, the pore size distribution of GZC-U and GC-U is as follows Figure 2 The pore size is mainly concentrated between 0.5-2.1nm, indicating that the sample GZC-U is a mesoporous material. The specific surface area of ​​GC-U is 4.8855m 2 / g, the pore volume is 0.0012ml / g, and the specific surface area of ​​GZC-U is 279.3609m 2 / g, and the pore volume is 0.1212ml / g. This shows that GZC-U has a good specific surface area and pore size, and the abundant micropores provide a large amount of adsorption space for the adsorption of the dye methylene blue, which greatly improves the adsorption performance of methylene blue.

[0062] (2) Scanning electron microscopy

[0063] Take samples GC, GC-U, GZC-U for X-ray diffraction spectrum analysis and scan them into the X-ray diffractometer. Scanning speed 5°min -1 , scanning range 5-70°.

[0064] Depend on Figure 3 It can be seen that sugarcane bagasse (GC) has an obvious fiber structure and basically no pore structure on the surface; Figure 4 It can be seen that a porous structure appears when urea is added to the mixture; Figure 5 After adding ZnCl2, obvious, diverse and complex pore structures appeared on the surface, and the pores increased significantly. This is due to certain shrinkage and cracking after high-temperature carbonization. Secondly, it can be proved that the use of ZnCl2 can change the morphology of the fiber and promote the formation of pores on the surface of porous carbon materials, providing porous carbon with a larger specific surface area and adsorption sites, thereby improving the adsorption performance of pollutants.

[0065] (3) X-ray diffractometer

[0066] Take samples GC, GC-U, GZC-U, and perform X-ray diffraction spectrum analysis, and scan them into the X-ray diffractometer. The scanning speed is 5°min-1, and the scanning range is 5-70°.

[0067] Depend on Figure 6 It can be seen that the XRD diffraction spectra of GC and GC-U are similar, with obvious diffraction peaks when 2θ is equal to 20° to 30°, and (002) and (100) crystal plane diffraction peaks, indicating that the sample has a certain graphite microcrystalline structure and the surface active carbon skeleton is amorphous. Compared with the other two, the XRD diffraction spectrum of GZC-U shows multiple peaks with different intensities and independent of each other. The more continuous and sharp the peaks in the figure, the better the crystallinity of the material. This shows that the use of ZnCl2 has a significant effect on the composition and crystal structure of biochar.

[0068] (4) Thermogravimetric analyzer

[0069] Thermogravimetric analyzer uses program temperature adjustment to detect the changing trend of material mass and temperature or time. Take samples GC, GC-U, GZC-U, and measure the relative content of each element by observing the volatilization of each element during the heating and cooling process of the sample. The temperature range is 30-1000℃, and the heating rate is 20℃ / min.

[0070] Depend on Figure 7 It can be seen that the fiber mass of GC, GC-U and GZC-U decreases with the increase of temperature. The remaining amount of GC is 76.25%, the remaining amount of GC-U is 72.51%, and the remaining amount of GZC-U is 49.18%. The main changes of GZC-U are divided into three stages, which are 47℃, 214℃ and 559.4℃ respectively. The mass loss in the first stage is mainly caused by the volatilization of bound water and free water in the sample; the mass loss in the second stage is mainly caused by the decomposition of lignin, cellulose and hemicellulose in the original fiber; the third stage is the main process of mass loss, which has nothing to do with carbonate inorganic salts, and most substances will undergo corresponding gasification reactions at high temperatures, so the final products are only ash and fixed carbon. The formation of biochar pores in the entire pyrolysis process is mainly caused by the evaporation of substances such as carbon dioxide and water vapor.

[0071] (5) Fourier transform infrared spectrometer

[0072] Take samples of GC, GC-U, and GZC-U, weigh and mix them with KBr in a ratio of 1:100, grind them in an agate mortar, and make them into round pieces with a tablet press. Use Fourier transform infrared spectroscopy to scan at a speed of 4 cm / min. -1 , detection range is 4000-500cm -1 .

[0073] Depend on Figure 8 It can be seen that GC at 1574cm -1 An absorption peak appears, which is the vibration peak of CC bond; GC-U at 1582cm -1 An absorption peak appears, which is also the vibration peak of CC bond; the range is 1600-1500cm -1 The main vibration peak is the CC bond. Compared with GC and GC-U, GZC-U is at 3456cm -1 、3570cm -1 There are absorption peaks. 1568cm -1 The vibration peak of CC bond is 3456cm -1 The peak at 3570 cm is the stretching vibration peak of -NH. -1 The stretching vibration peak of -OH is at . In summary, GZC-U has been successfully doped with N and has more functional groups, including amino and hydroxyl groups. The oxygen-containing functional groups show hydrophilicity, which is conducive to adsorption behavior.

[0074] 4. Application and implementation of adsorbent

[0075] 1. Experimental methods

[0076] Add the adsorbent to the methylene blue solution and conduct an intermittent adsorption experiment.

[0077] 2. Calculation method

[0078] The following formula can be used to calculate the adsorption rate η of methylene blue per unit gram weight of porous carbon.

[0079]

[0080] In the above formula, C0 is the initial concentration of the methylene blue solution, mg / L; Ct is the concentration of methylene blue in the supernatant at the tth moment, mg / L, min; η is the adsorption rate of the porous carbon material to the dye, %.

[0081] 3. Preparation of methylene blue standard curve

[0082] Accurately weigh 1.0000g of methylene blue powder, dissolve it and add it to a 1L volumetric flask, then add distilled water until the mark is reached. Use a pipette to add the dye to 5 100mL volumetric flasks and dilute them to five different concentrations. Use a UV spectrophotometer to measure the absorbance of methylene blue solutions at different concentrations, and use linear fitting to obtain the relationship between methylene blue concentration and absorbance, and draw a methylene blue standard curve. Fig. 9 There is a good linear relationship between the concentration of methylene blue and the absorbance. The linear regression equation is y = 0.2305x-0.1241, R 2 =0.9992.

[0083] 4. Adsorption experiment

[0084] (1) Adsorption of samples by adsorbents No. 1 to 5

[0085] Weigh 30 mg of sample and add it to 100 mg / L methylene blue solution with pH = 7. Adsorb it in a magnetic heating stirrer for 1 hour, filter it, measure the absorbance at a wavelength of 665 nm, and calculate the adsorption rate.

[0086] Depend on Fig.10 It can be seen that the adsorption rates of adsorbent samples No. 1 to No. 5 of the present invention are all above 76%, which are better than the 61% of the current technology. As the ratio of urea to bagasse increases, the adsorption rate shows a trend of first rising and then falling. When the urea to bagasse is 62.5%, the adsorption rate of porous carbon on methylene blue reaches a maximum of 91.93%. This is because nitrogen atoms are doped in the carbon material, and the addition of urea will lead to the formation of nitrogen-containing functional groups, improve its hydrophilic properties and pore structure. As the ratio increases, the active sites on the surface of porous carbon increase, and the adsorption effect on methylene blue increases. When the adsorption equilibrium is reached, even if the ratio continues to increase, the adsorption rate will not continue to rise because the concentration of methylene blue remains unchanged. Therefore, the optimal urea / bagasse ratio is 62.5%.

[0087] (2) Adsorption of samples with adsorbents No. 6 to 10

[0088] Weigh 30 mg of sample and add it to 100 mg / L methylene blue solution with pH = 7. Adsorb it in a magnetic heating stirrer for 1 hour, filter it, measure the absorbance at a wavelength of 665 nm, and calculate the adsorption rate.

[0089] Depend on Fig.11 It can be seen that the adsorption rates of adsorbent samples No. 6 to No. 10 of the present invention are all above 70%, which are better than the 61% of the current technology. With the increase of carbonization temperature, the adsorption of methylene blue by porous carbon first increases and then decreases. When the carbonization temperature is 500°C, the adsorption rate of porous carbon is as high as 84.25%. This is because carbonization, also known as thermal cracking, is heated in a nitrogen atmosphere to remove volatile substances and produce a high-carbon solid product suitable for activation with initial pores. As the temperature increases, the density of the particles decreases, chemical bonds break under high temperature conditions, and other substances such as free radicals are generated. This is not conducive to the adsorption of methylene blue, and the adsorption rate decreases. Therefore, the optimal carbonization temperature is 500°C.

[0090] (3) Adsorption of samples with adsorbents No. 11 to 15

[0091] Weigh 30 mg of sample and add it to 100 mg / L methylene blue solution with pH = 7. Adsorb it in a magnetic heating stirrer for 1 hour, filter it, measure the absorbance at a wavelength of 665 nm, and calculate the adsorption rate.

[0092] Depend on Fig.12 It can be seen that the adsorption rates of adsorbent samples No. 11 to 15 of the present invention are all above 87%, which are better than the 61% of the current technology. As the carbonization time increases, the adsorption rate of porous carbon to methylene blue increases, and begins to decrease when the carbonization time exceeds 2 hours. When the carbonization temperature is 2 hours, the best adsorption rate to methylene blue is 92.84%. This is because as time increases, during the nitrogen doping process, the molecular vibration of organic matter begins to intensify, thermal decomposition reaction occurs, and the adsorption with methylene blue is rapid, and the adsorption rate increases; however, as time continues to increase, the surface of porous carbon undergoes cracking and shrinkage, the concentration of methylene blue remains unchanged, the adsorption rate decreases, and the adsorption capacity is poor. Therefore, the best carbonization time is 2 hours.

[0093] From the adsorption test results of (1) to (3), it can be seen that sample No. 13 of the present invention has the best adsorption effect on the methylene blue solution. Sample No. 13 is taken to continue the next step of adsorption experiment research.

[0094] (4) Different amounts of adsorbent added

[0095] The initial concentration of methylene blue solution was 100 mg / L, the adsorption time was 1 h, the solution pH was 7, and the addition amount of sample No. 13 was 10, 20, 30, 40, 50, and 60 mg. Oscillating adsorption was performed in a desktop constant temperature oscillator, and the sample was taken out and filtered, and the absorbance was measured at a wavelength of 665 nm to calculate the adsorption rate.

[0096] like Fig.13 As shown, the adsorption rate of sample adsorbent No. 13 reached more than 92.5% at an addition amount of 10 to 60g. With the increase of the addition amount, the adsorption rate reached 94.65% when the addition amount was 30mg, and the adsorption rate of porous carbon on methylene blue gradually increased. However, with the increase of the addition amount of porous carbon, the adsorption rate of methylene blue decreased. This is because the adsorption sites increase with the increase of the addition amount, but since the mass concentration of methylene blue remains unchanged, the adsorption amount of porous carbon per unit mass will decrease. It can be seen that the addition amount of 30mg is the best.

[0097] (5) Methylene blue solutions with different initial concentrations

[0098] The addition amount of sample No. 13 was 30 mg, the adsorption time was 1 h, the solution pH was 7, and the initial concentration of methylene blue was 100, 200, 300, 400, 500, and 600 mg / L. The sample was oscillated and adsorbed in a tabletop constant temperature oscillator, and then filtered and the absorbance was measured at a wavelength of 665 nm to calculate the adsorption rate and adsorption amount.

[0099] like Fig.14As shown in the figure, the adsorption rate of sample No. 13 adsorbent for treating 50-600 mg / L methylene blue solution reached more than 92%. With the increase of initial concentration, the adsorption rate at adsorption equilibrium gradually increased, and when the concentration was 400 mg / L, the adsorption rate reached 98.51%. When the concentration of methylene blue exceeded 400 mg / L, the adsorption rate began to decrease. This is because the adsorption sites of porous activated carbon are limited. With the increase of concentration, the adsorption sites on the activated carbon are gradually occupied by methylene blue, and the adsorption rate begins to decrease. Therefore, the initial concentration of 400 mg / L has the best adsorption effect.

[0100] (5) Different adsorption time

[0101] The addition amount of sample No. 13 was 30 mg, the pH of the methylene blue solution was 7, the initial concentration of methylene blue was 400 mg / L, and the adsorption time was 1 h, 1.5 h, 2 h, 2.5 h, and 3 h. The sample was oscillated and adsorbed in a desktop constant temperature oscillator, and then filtered and the absorbance was measured at a wavelength of 665 nm to calculate the adsorption rate.

[0102] like Fig.15 As shown, the adsorbent of the present invention has an adsorption rate of more than 98.10% in 30 to 180 minutes. As the adsorption time increases, the adsorption rate of methylene blue increases sharply. When the adsorption time is greater than 60 minutes, the methylene blue reaches adsorption equilibrium. This is because the adsorption sites on the porous carbon surface are limited, the initial concentration remains unchanged, the adsorption rate increases within a certain period of time, and the adsorption time increases but the adsorption rate no longer increases significantly and gradually stabilizes. It can be seen that the optimal time for adsorption should be 60 minutes.

[0103] (6) Methylene blue solutions at different pH values

[0104] The addition amount of sample No. 13 was 30 mg, the initial concentration of methylene blue was 400 mg / L, the adsorption time was 1 h, and the pH was 1, 3, 5, 7, 9, and 11. The sample was oscillated and adsorbed in a desktop constant temperature oscillator, and then filtered and the absorbance was measured at a wavelength of 665 nm to calculate the adsorption rate.

[0105] like Fig.16 As shown in the figure, with the increase of pH, the removal rate of methylene blue by the adsorbent of the present invention gradually increases, and when the pH is equal to 7, the removal rate increases rapidly. When the pH is greater than 7, the overall upward trend is still present, but it is slower. This is because methylene blue is a cationic dye, which exists in the solution in a cationic state and is easily combined with the adsorbent with negatively charged groups on the surface to interact and be adsorbed, and the more negatively charged groups on the surface of the adsorbent, the more favorable it is for the adsorption of methylene blue. Under acidic conditions, the groups on the surface of the activated carbon will react with the H in the solution. +In combination, as the pH of the solution increases, the number of negatively charged groups on the surface of the activated carbon increases, which is beneficial to the adsorption of methylene blue and the removal rate becomes higher and higher.

[0106] 5. Adsorption kinetics analysis

[0107] The addition amount of sample No. 13 is 30 mg, the solution pH is 7, the initial concentration of methylene blue is 400 mg / L, and the adsorption time is 60, 90, 120, 150, and 180 min. Oscillate and adsorb in a desktop constant temperature oscillator, take out and filter, measure the absorbance at a wavelength of 665 nm, and calculate the adsorption rate. The calculation formulas of the pseudo-first-order kinetic model and the pseudo-second-order kinetic model are as follows:

[0108] ln(q e -q t )=lnq e -k1t

[0109]

[0110] In the above formula, q e represents the adsorption amount of methylene blue by porous carbon when reaching equilibrium, mg / g; q t represents the adsorption of methylene blue by porous carbon at time t, mg / g; k1 represents the pseudo-first-order kinetic constant, min -1 ; k2 represents the pseudo-secondary adsorption rate constant, g / (mg·min).

[0111] like Fig.17 , Fig.18 As shown in Table 2, the pseudo-first-order kinetics R 2 The R of pseudo-second-order kinetics is 0.8703. 2 is 0.9957. Compared with pseudo-first-order kinetics, pseudo-second-order kinetics has a higher R 2 Value. Quasi-secondary q e The value is 1355.63 mg / g, while the pseudo-first-class q e The value is 2210.55 mg / g, which is closer to the experimental value than the pseudo-second-order kinetics, indicating that the process is chemical adsorption.

[0112] Table 2 Parameters of the kinetic model for the adsorption of methylene blue on porous carbon

[0113]

[0114] 6. Adsorption isotherm analysis

[0115] The addition amount of sample No. 13 is 30 mg, the adsorption time is 1 h, the solution pH is 7, and the initial concentration of methylene blue is 100, 200, 300, 400, 500, 600 mg / L. Set the temperature to 25 ° C in the desktop constant temperature oscillator for oscillation adsorption, take out and filter, measure the absorbance at a wavelength of 665 nm, and calculate the adsorption rate and adsorption amount. The methods for 30 ° C and 35 ° C are the same as above. The Langmuir isotherm adsorption equation and the Friedrich isotherm adsorption equation are as follows:

[0116]

[0117] In the above formula: q m is the maximum adsorption capacity, mg / g; q e is the adsorption capacity at adsorption equilibrium, mg / g; k L is the adsorption equilibrium constant of the Langmuir isotherm adsorption model; k F is the adsorption equilibrium constant of the Friedrich isotherm adsorption model. C e is the concentration of the adsorbate after adsorption equilibrium, mg / L; n refers to the Friedrich adsorption intensity; C t Refers to the adsorbate concentration at time t, mg / L.

[0118] Depend on Fig.19 and Fig. 20 The fitting diagram of and the isothermal model parameters of Langmuir and Friedrich in Table 3 show that the porous carbon in the Langmuir model undergoes monolayer adsorption at specific sites, while the Friedrich model shows that adsorption occurs on heterogeneous surfaces and the binding sites are unequal. The R 2 (0.9855-0.9981) than the R of the Friedrich model 2 (0.9504-0.9607) is high, indicating that methylene blue is uniformly adsorbed on the porous carbon. It is more consistent with the Langmuir model and is a single-layer adsorption.

[0119] Table 3 Isotherm adsorption model fitting parameters

[0120]

[0121] The above embodiments are only specific examples for further describing the purpose, technical solutions and beneficial effects of the present invention, and the present invention is not limited thereto. Any modification, equivalent replacement, improvement, etc. made within the scope disclosed by the present invention are included in the protection scope of the present invention.

Claims

1. A method for improving the adsorption efficiency of methylene blue, characterized in that: The adsorbent is prepared by using bagasse as a carbon source, urea as a nitrogen source and ZnCl2 as an activator. The adsorbent is added into a methylene blue solution with a certain mass concentration and adsorbed for a period of time to obtain a clear solution. The mass ratio of urea to bagasse is (1-3):4, and the mass ratio of ZnCl2 to bagasse is 2:

1.

2. A method for improving the adsorption efficiency of methylene blue according to claim 1, characterized in that: The mass ratio of the urea to bagasse is 2.5:

4.

3. A method for improving the adsorption efficiency of methylene blue according to claim 1, characterized in that: The bagasse is dry bagasse.

4. A method for improving the adsorption efficiency of methylene blue according to claim 1, characterized in that: The adsorbent is added in an amount of 10 to 30 mg per 100 ml of methylene blue solution.

5. A method for improving the adsorption efficiency of methylene blue according to claim 1, characterized in that: The initial mass concentration of the methylene blue solution is 100-600 mg / L, and the pH value of the solution is 1-11.

6. A method for improving the adsorption efficiency of methylene blue according to claim 1, characterized in that: The adsorption time is 30 to 80 minutes.

7. A method for improving the adsorption efficiency of methylene blue according to any one of claims 1 to 6, characterized in that: The preparation method of the adsorbent: (1) Mixing: Grind and mix bagasse and urea according to the mass ratio; (2) Impregnation: adding water and ZnCl2 to the mixture of step (1) according to the mass ratio for impregnation; (3) Stirring: Stir the impregnated material at room temperature and then dry it to constant weight; (4) Carbonization: The dried material is subjected to high temperature carbonization treatment at 400-800°C for 1-3 hours, and then washed and dried to obtain an adsorbent.

8. A method for improving the adsorption efficiency of methylene blue according to claim 7, characterized in that: The solid-liquid ratio of the mixture to water is (5-7) g:50 ml.

9. A method for improving the adsorption efficiency of methylene blue according to claim 7, characterized in that: The time of stirring at room temperature is 25 to 30 minutes.

10. A method for improving the adsorption efficiency of methylene blue according to claim 7, characterized in that: The immersion time is 25 to 30 minutes.

Citation Information

Patent Citations

  • Nitrogen-doped porous carbon and preparation method and application

    CN109573976A

  • Preparation method of nitrogen-containing porous carbon based on juteand application of nitrogen-containing porous carbon

    CN110627065A

  • Nitrogen-containing oxygen-enriched lignin-based porous carbon as well as preparation and application thereof in carbon dioxide adsorption

    CN116040629A

  • Preparation method of nitrogen-doped porous bagasse biochar

    CN117361527A

  • KR20230013944A